Translation and validation of the Pediatric Daytime Sleepiness Scale (PDSS) into Brazilian Portuguese - Carniel J.D.* (2016)
© 2015 Sociedade Brasileira de Pediatria.Objective The aim of this study was to translate and validate the Pediatric Daytime Sleepiness Scale (PDSS) into Brazilian Portuguese. Methods The translation/validation process was carried out through translation, back translation, technical review, assessment of verbal comprehension/clarity of the scale by experts and a focus group, test-retest, and application of the tool. The reproducibility analysis was performed by applying the PDSS in test-retest; internal consistency was verified by applying the scale in 90 children and adolescents. Results The mean score of the sum of PDSS questions was 15.6 (SD = 5.0) points. The PDSS showed appropriate indicators of content validation and clarity for the Brazilian Portuguese version. The internal consistency analysis showed a Cronbach's alpha of 0.784. The PDSS showed adequate reproducibility. The PDSS scores showed a significant and negative correlation with time spent in bed (r = -0.214; p = 0.023). Conclusion The Brazilian Portuguese version of the PDSS shows satisfactory indicators of validity and can be applied in clinical practice and scientific research.